Mild dealumination of H-ZSM-5 zeolite for enhanced conversion of glucose into 5-hydroxymethylfurfuralin a biphasic solvent system - Ojelabi, Oluwaseyi; Yousatit, Satit; Rashid, Umer; Ngamcharussrivichai, Chawalit (Multidisciplinary Digital Publishing Institute, 2023)
Transformation of lignocellulosic biomass into high-value chemicals is a viable strategy for sustainable development of a bio-based economy. 5-Hydroxymethylfurfural (HMF) is one of potential platform bio-chemicals for the manufacture of various renewable products. In this work, a commercial H-ZSM-5 zeolite was used as a starting material for preparing a series of acid catalysts with bifunctionality for direct dehydration of glucose to HMF in a biphasic water/tetrahydrofuran system. The pristine H-ZSM-5 was mildly dealuminated by refluxing with dilute nitric acid solutions to adjust its acid properties. Although the acid treatment slightly altered the elemental composition, textural properties, and morphology of zeolite, the total acidity and distribution of acid sites were significantly modified. Some non-framework aluminum (Al) oxide clusters were removed from the parent H-ZSM-5 simultaneously with a partial hydrolysis of zeolitic framework. An increased fraction of coordinatively unsaturated framework Al species enhanced the number of Lewis acid sites. Using 0.1 M solution in the treatment provided the suitable catalyst (0.1DeAl.H-ZSM-5), giving a glucose conversion and HMF yield of >99 and 64.7, respectively, and a good reusability under the optimized reaction conditions. These results show the industrial potential of the proposed method for simple but efficient preparation of H-ZSM-5 catalysts for producing HMF via the catalytic dehydration of glucose.